A Phenomenological Study on the Journeys of African American Female Academic Leaders in Technical Colleges - Wilkerson, Patsy G. (My University, 2019)
This phenomenological study examines the experiences of African American female academic leaders who blazed the trail in technical colleges in a southern state. The research approach was a qualitative phenomenological study implemented through guided interview questions using Seidman’s (2013) three-stage approach. Three-stage interviews and phenomenological data analysis were conducted with five African American female academic leaders. The results are presented in profiles in this study with each African American female academic leader sharing their stories and experiences of rising up into the ranks of leadership in technical colleges rooted in the South. Some of the themes that I found were related to (1) their personal and professional backgrounds, (2) their career experiences, and (3) the skills, attributes and strategies each believed to have been an asset in their careers.
Chapter I: INTRODUCTION 1 -- Background 5 -- Statement of the Problem 7 -- Topic and Purpose of this Study 9 -- Significance of the Study 10 -- Chapter II: LITERATURE REVIEW 14 -- Critical Race Theory 14 -- Resilience Theory 19 -- Othermothering 22 -- Summary of Theories 24 -- Survey of Published Literature 24 -- Leadership in higher education. 24 -- Challenges 25 -- Mentoring 26 -- Survey of Dissertations 27 -- Chapter III: METHODOLOGY 30 -- Participants 33 -- Phenomenological Data Collection 36 -- Phenomenological Interviews 37 -- Phenomenological Data Analysis 41 -- Validity 45 -- Chapter IV: RESULTS 47 -- Anna’s Profile 49 -- Becky’s Profile 58 -- Carley’s profile 69 -- Debra’s Profile 72 -- Eva’s Profile 81 -- Chapter V: THEMES 91 -- Family Background 93 -- Anna 93 -- Becky 94 -- Carley 94 -- Debra 94 -- Eva 94 -- Early Childhood School Systems 95 -- Anna 95 -- Becky 95 -- Carley 96 -- Debra 96 -- Eva 96 -- Initial Career Goal 97 -- Anna 97 -- Becky 97 -- Carley 98 -- Debra 98 -- Eva 98 -- Professional Background 99 -- Anna 99 -- Becky 99 -- Carley 99 -- Debra 99 -- Eva 100 -- Personal Challenges Early in Life 100 -- Anna 100 -- Becky 101 -- Carley 101 -- Debra 101 -- Eva 101 -- Climbing the Ladder 104 -- Anna 104 -- Becky 105 -- Carley 105 -- Debra 105 -- Eva 106 -- It’s Complicated 107 -- Anna 107 -- Becky 107 -- Carley 107 -- Debra 108 -- Eva 108 -- Mentor. What’s the Big Deal? 109 -- Anna 109 -- Becky 109 -- Carley 110 -- Debra 110 -- Eva 110 -- Challenges 111 -- Anna 111 -- Becky 112 -- Carley 112 -- Debra 112 -- Eva 113 -- Passion for Students 116 -- Anna 116 -- Becky 116 -- Carley 117 -- Debra 117 -- Eva 117 -- Leadership Skills 118 -- Anna 118 -- Becky 119 -- Carley 119 -- Debra 120 -- Eva 120 -- Value Education 121 -- Anna 121 -- Becky 122 -- Carley 122 -- Debra 122 -- Eva 122 -- Resilience 123 -- Anna 123 -- Becky 123 -- Carley 124 -- Debra 124 -- Eva 124 -- Chapter VI: CONCLUSION 126 -- Interpretation of the Findings 128 -- Limitations 132 -- Recommendations for Future Research 132 -- Implications 133 -- REFERENCES 134 -- Appendix A: Institutional Review Board Approval 139 -- Appendix B: Informed Consent Script 141 -- Appendix C: Interview Guide 145.
Keywords: Dissertations, Academic--United States; Academic achievement; Technical institutes; Leadership in minority women; Southern States; Interviews; African American women